Corporate education and digital inclusion in the public administration scenario - Guedes, Elieti Cadamuro; Cruz, Julio Cesar Tomasi (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article has as main idea the Corporate Education for the promotion of digital inclusion in the Public Administration scenario. Corporate education is born as an improvement of traditional training, aiming at the continuous training of the company's employees. Digital inclusion and technologies are closely related and important for both the organization and the collaborator. The methodology adopted by the authors was bibliographic research. Although the public sector has several technologies, many employees still do not know how to use it, so this sector has much to develop in relation to corporate education, information and communication technologies, and digital inclusion itself.